Pengembangan E-Modul Pendidikan Agama Islam Dengan Smart Apps Creator Berbasis Pendekatan Game Method Di SMK Muhammadiyah 1 Kalirejo - Diani, Eva Riantika; Ulya , Inarotul; Riskia, Anisa (Institut Agama Islam Darul Fattah Lampung, 2025)
This research aims to develop an Islamic Religious Education (PAI) E-Module based on the Game Method approach using the Smart Apps Creator (SAC) application for Muamalah (Mutual Assistance) material at SMK Muhammadiyah 1 Kalirejo. This development was motivated by low student enthusiasm for the PAI learning process, which was considered boring and less interactive. This study employed the Borg & Gall Research and Development (R&D) model (modified) with seven stages. Data collection instruments included validation by material and media experts, teacher assessments, and student response questionnaires. The validation results obtained an average feasibility score of